Postoperative increase in grey matter volume in visual cortex after unilateral cataract surgery. (22nd November 2011) - Lou, Astrid R.; Madsen, Kristoffer H.; Julian, Hanne O.; Toft, Peter B.; Kjaer, Troels W.; Paulson, Olaf B.; Prause, Jan U.; Siebner, Hartwig R.
Abstract. Purpose: The developing visual cortex has a strong potential to undergo plastic changes. Little is known about the potential of the ageing visual cortex to express plasticity. A pertinent question is whether therapeutic interventions can trigger plastic changes in the ageing visual cortex by restoring vision. Methods: Twelve patients aged 50–85 years underwent structural high‐resolution T1‐weighted MRI of the whole brain 2 days and 6 weeks after unilateral cataract surgery. Voxel‐based morphometry (VBM) based on T1‐weighted magnetic resonance imaging (MRI) was employed to test whether cataract surgery induces a regional increase in grey matter in areas V1 and V2 of the visual cortex. Results: In all patients, cataract surgery immediately improved visual acuity, contrast sensitivity and mean sensitivity in the visual field of the operated eye. The improvement in vision was stable throughout the 6 weeks after operation. VBM revealed a regional expansion of grey matter volume in area V2 contralateral to the operated eye during the 6‐week period after surgery. Individual increases in grey matter were predicted by the symmetry in visual acuity between the operated eye and nonoperated eye. The more symmetrical visual acuity became after unilateral cataract surgery, the more pronounced was the grey matter increase in visual cortex. Conclusion: The data suggest that cataract surgery triggered a use‐dependent structural plasticity in V2 presumably through improved binocular integration of visual input from both eyes. We conclude that activity‐dependent cortical plasticity is preserved in the ageing visual cortex and may be triggered by restoring impaired vision.